Pengaruh Penerapan Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Di MTS Al-Huda Mardiharjo - Rossa Ayuni; Duharman Duharman (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of this research is: 1) to find out the application of discovery learning models in MTs Al-Huda Mardiharjo. 2) to find out the student learning results at MTs Al-Huda Mardiharjo. 3) to determine the effect of the application of Discovery Learning learning model on student learning outcomes at MTs Al-Huda Mardiharjo. The population in this study was the entire class of MTs Al-Huda Mardiharjo which amounted to 5 classes. The sample selected is class VII, class VII.1 as the experiment group and class VII.2 as the control group. The instruments used in this study are written tests. Data collection techniques in the form of observations, tests, and documentation. The analysis method is used using the SPSS program. The results showed that students' study results were categorized as high with an average score of 7.81. T-test results obtained a significant value of 0.003 less than 0.05 (sig: 0.003 < 0.05)and T count 3,149more than T table 2,006 (sig: 3,149 > 2,006) as well as the influence of discovery learning model on student learning outcomes at MTs Al-Huda Mardiharjo by 30.6%. So it can be concluded that there is an influence of Discovery Learning learning model on the learning outcomes of students at MTs Al-Huda Mardiharjo.